Brain damage and global stereopsis. - Cowey, A; Porter, J (1979)
When a single object lies in front of or beyond the plane of fixation its retinal image lies on disparate positions in the two eyes. This 'local' retinal disparity is an excellent cue to depth, and retinal disparties of a few seconds of arc are detectable by people and monkeys. However, most visual scenes produce a complex array of contours in each eye and we can detect the disparity in the arrays despite the ambiguous nature of the disparities, i.e. each contour in one eye could be related to any of several similar contours in the other eye. This ability, known as 'global' stereopsis, may be selectively impaired following brain damage in man. Global stereopsis was measured in rhesus monkeys before and after removing a different cortical visual area in different groups of animals. Only removal of the inferotemporal cortex impaired global stereopsis. The result is related to the findings with human patients and to receptive field properties of neurons in the inferotemporal cortex of monkeys.